IMPROVING QUR’ANIC MEMORIZATION THROUGH AN AUDIOVISUAL APPROACH: A QUALITATIVE STUDY AT SDIT AKMALA SABILA CIREBON - Indah Darojah; Nurlela; Moh Ali (Jurnal Cakrawala Pendas, 2026)
This study aims to analyze efforts to improve Qur’anic memorization through an audiovisual approach at SDIT Akmala Sabila, Talun District, Cirebon Regency. The research employs a qualitative approach with a case study design to explore in depth the implementation of audiovisual-based tahfidz learning. The participants include the school principal, tahfidz teachers, and students. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the audiovisual approach significantly enhances students’ Qur’anic memorization quality in terms of fluency, tajwid accuracy, memory retention, and learning motivation. The use of audiovisual media such as murottal videos, verse visualization, and repeated audio provides multisensory stimulation that strengthens students’ cognitive processes. Additionally, this approach increases student engagement and interest while enabling teachers to deliver learning materials more effectively and interactively. Supporting factors include the availability of facilities, teacher competence, and institutional support, whereas inhibiting factors involve limited infrastructure and technical issues. This study concludes that the audiovisual approach is an effective, innovative, and relevant learning strategy for improving Qur’anic memorization in Islamic elementary schools and can serve as an alternative model for tahfidz learning in the digital era.